Exploration of Investment Risk Causes and Prevention Measures in Real Estate Enterprises - Fang, Zhen (Transactions on Economics, Business and Management Research, 2024)
In China's national economic system, the real estate industry is a pillar industry that not only directly relates to the growth of the national economy but also profoundly affects the quality of life of the general populace and the stable development of society. In recent years, with the increasingly complex global economic environment, frequent adjustments in national macro policies, and intensified market competition, real estate enterprises face new challenges. Investment, as the core driving force for profit growth and sustainable development of real estate enterprises, is undeniably important. However, investment itself is a high-risk activity, especially in the real estate industry, where various risk factors such as market fluctuations, policy changes, financial pressures, and management mistakes can pose significant challenges and even lead to investment failures. Therefore, it is crucial to deeply analyze and study the types and causes of investment risks in real estate enterprises, and to formulate and implement targeted and effective risk prevention measures to ensure the health and stability of the entire real estate industry, as well as the continuous growth of the national economy and the improvement of people's livelihoods.